The needs analysis of the marriage education program for Turkish Cypriot community: Development phase - Salman, Nihal; Batman, Kemal Akkan; Sorakin, Yasemin (Frontiers in Psychology, 2022)
Abstract This research is a needs analysis for the development of a marriage education program in the TRNC. The aim of the research is to compare the views of married and divorced individuals about marriage education and to determine their needs for marriage education. For this purpose, it has been determined in which subjects they see themselves as sufficient or inadequate, in which subjects they are willing to participate in the training and in which subjects they are unwilling. In this study, embedded design, one of the mixed research methods in which qualitative and quantitative methods are used together, was used. In the qualitative aspect of the research, the sample group was studied with 16 married and divorced participants living in the TRNC. In the quantitative dimension, a total of 385 married or divorced participants were consulted using the sample calculation of unknown universe. The findings are as follows; In both quantitative and qualitative dimensions, the majority of the participants think that if marriage education is given, they can have a healthier and happier marriage. A training program will be developed for these determined subjects and will be applied to 20 participants in a semi-experimental model through the TRNC Ministry of National Education.